(untitled) (Fiep Bulletin - online, 2015)
The object of this study is a gymnastics program and questions instructed corporal exercises conducted during work hours at a factory. The analysis is supported by data gathered in interviews, observations and various other types of instruments. It adopts a theoretical approach that supports the elaboration of an empiric category: labor gymnastics as technology for organizing labor, and not as a leisure activity. This practice is found to constitute a technology because it subjectively controls human beings. The gymnastics program is oriented by playful activities and seeks to establish an organic equilibrium in workers. The need is recognized to be properly prepared for the high productive requirement of labor relations. In this way a conjugation is established between the physiological equilibrium and the capacity to produce more and better. Nevertheless, it was seen that the principal consequence for the internal process of labor is to achieve a greater general disposition and not only an organic one. It was also perceived that the idea is promoted that since exercise is a corporal practice, it can be considered to be a leisure activity. As a result, it is essential that we make explicit that leisure, although it has a common root human activity with work, is different from work. Since leisure is a consequence of the social division of labor, it should not be explained by feelings or sensations (pain or pleasure) but by the type of social relationship that is established in the activity involved.